COMMODITY ASPECTS OF INFORMATION PROVISION OF ASSORTMENT ITEMS - DRAZHNYTSIA, Serhii; KALINSKY, Evgen (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In this article, the authors define the role and tasks of information support for assortment items and the process of their management, and also highlight the place of commodity-related aspects of information support for assortment items. It has been established that for effective management of assortment items and product flows, high-quality information support is necessary, which can be based, among other things, on commodity aspects. The authors cite the dependence of the effectiveness of trade and intermediary sales activities on the quality and completeness of information provision of assortment items as a source of relevant information regarding their features and rules for handling them. The better the information support, the more effective the assortment and sales policy of trading enterprises will be.The authors also conducted a brief analysis of the main sources of information support for product lines in the article. It was established that recently the sources of information provision for assortment items are, for the most part, their descriptions in publicly available information resources, accompanying documents, partly in standards, as well as one’s own experience and ideas. Under such conditions, in the process of organizing sales and managing the assortment of goods, information on the product identification of goods is not fully used, which reduces the quality of information support for assortment items.Based on the analysis conducted, the authors proposed, in order to improve and increase the quality of information support for assortment items and the assortment policy of a trading enterprise as a whole, to use information on the product identification of goods. Detailed commodity identification descriptions of assortment items, filling the information support of assortment policy with new content and increasing its quality, allow us to significantly improve and raise the level of efficiency in the formation of assortment management and sales strategies.
Keywords: information; information support; commodity aspects; commodity identification; assortment positions